2016
DOI: 10.2147/ott.s113724
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous basal cell carcinoma arising within a keloid scar: a case report

Abstract: Basal cell carcinomas (BCCs) are one of the most frequent cutaneous malignancies. The majority of BCCs are reported to occur on the auricular helix and periauricular region due to ultraviolet light exposure. Despite the frequency of BCCs, those that develop within scar tissue are rare, and the phenomenon of keloid BCCs has rarely been reported in the literature. Keloid collagen within BCCs is associated with morphoeiform characteristics, ulceration, or necrosis. Extensive keloid collagen is often seen in BCCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It was found that inhibition of mTOR can reduce extracellular matrix deposition [ 20 , 21 ]. In addition, the expression of mTOR and its upstream molecules PI3K and Akt were significantly increased in keloid tissues [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that inhibition of mTOR can reduce extracellular matrix deposition [ 20 , 21 ]. In addition, the expression of mTOR and its upstream molecules PI3K and Akt were significantly increased in keloid tissues [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The observations are consistent with disturbance being a fundamental factor [93] in tumour initiation. Further, an association between keloids and cancer has been reported [112, 113]. There are, of course, many occasions where scars are not sites of subsequent tumour growth, probably reflecting that for cancerous behaviour to occur, the disturbance of ECM must be accompanied by a loaded tissue-specific oncogene that has potential to elicit uncontrolled proliferation in that tissue (Fig.…”
Section: Disrupted Ecm and Cancermentioning
confidence: 99%